2020
DOI: 10.3382/ps/pez522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cassava foliage on feed digestion, meat quality, and antioxidative status of geese

Abstract: As the by-product of cassava, cassava foliage (CF) has been widely used in livestock feed. However, little information is available on its utilization for geese. In this study, we aimed to investigate the effects of CF on the feed digestion, meat quality, and antioxidative status of geese. A total of 108 male Hainan indigenous geese (28-days-old) with similar body weight were randomly and evenly divided into 3 groups, and the geese were fed for 42 D on either the control diet (CON) consisting of ground maize, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Janicki et al also reported that semi-intensive feeding resulted in lesser monounsaturated and higher polyunsaturated fatty acids in abdominal fat [ 11 ]. Greater meat L * and b * in CON geese was in line with previous studies of higher breast meat b * and thigh meat L * values in poultry reared in a free-range system [ 23 , 30 , 32 ]. Shear force is used for evaluating tenderness of meat (samples with lower shear force are more tender).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Janicki et al also reported that semi-intensive feeding resulted in lesser monounsaturated and higher polyunsaturated fatty acids in abdominal fat [ 11 ]. Greater meat L * and b * in CON geese was in line with previous studies of higher breast meat b * and thigh meat L * values in poultry reared in a free-range system [ 23 , 30 , 32 ]. Shear force is used for evaluating tenderness of meat (samples with lower shear force are more tender).…”
Section: Discussionsupporting
confidence: 91%
“…Geese have a stronger gizzard than other waterfowl, making them successful grazers, able to break down and digest plant cell walls [ 14 , 23 ]. As degradation in the gizzard is largely mechanical, geese that accessed grazing pasture or were supplemented with roughage always had higher relative weights of gizzard and a longer digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…CF contains abundant nutrients, especially high levels of crude protein (CP) (16.41-22.68%). CF is widely used in animal feed in many countries, and it has great potential for improving the production performance of animals (Régnier et al, 2013;Napasirth et al, 2015;Li et al, 2017aLi et al, , 2020. Besides, CF harvest is seasonal, with higher quantity biomass in summer or rainy season.…”
Section: Introductionmentioning
confidence: 99%
“…Marcu et al [34] concluded that the increase in dietary protein levels significantly increased in pH values of muscle of broiler chickens. In contrast recently, Li et al [35] reported that using dietary cassava foliage as high protein content for Hainan China geese significantly (p < 0.05) decreased the level of pH 24 postmortem. The present study showed that moderate M + C gave the highest value of pH 24, which linked with meat quality as reported by Biesek, et al [36] who clarified that higher pH of goose meat is often associated with a higher water-holding capacity.…”
Section: Meat Compositionmentioning
confidence: 83%